Bułgarski car Piotr i jego żona Maria Lekapena w Latopisie Helleńskim i Rzymskim drugiej edycji - Brzozowska, Zofia A. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
The sequence concerning the reign of Peter and Maria Lekapene as well as the Byzantine-Bulgarian relations between 927 and 969 can be found in the second version of the Hellenic and Roman Chronicle. It is a vast historiographical work, whose authors attempted to demonstrate the history of medieval Rus against the broad background of universal history, drawing on the sources of Byzantine provenance known in Slavonic translation (mainly the chronicles of John Malalas and George Hamartolus). Given the fact that the Hellenic and Roman Chronicle does not contain information about the capture of Constantinople by the Ottoman Turks, the year 1453 is considered the terminus ante quem for the second version of the said chronicle, which is of interest to us here. Its oldest preserved copies come from the mid-fifteenth century. The passages about Maria and Peter are extensive. They include about six columns of text written in semi-uncial in the most representative copy of the second version of the Hellenic and Roman Chronicle, i.e. manuscript БАН, 33.8.13, which is dated to the last quarter of the fifteenth century. Reading them allows one to ascertain that they constitute only a reworded version of the Slavic translation of the relevant passages of the B-version of the Georgius Monachus Continuatus. The content of the Byzantine source is quoted here in full without any abbreviations or author’s additions. The differences between the text of БАН, 33.8.13 and the text of РГБ, собр. Ундольского [Ф. 310], № 1289 – constituting the basis for editing the translation of the Georgius Monachus Continuatus of the B-version – are limited only to the stylistic and editorial level, except for the changes resulting most probably from the copyist misunderstanding the meaning of the original.